Jordan Economic Monitor, Spring 2016 : The Challenge Ahead - World Bank (World Bank, Washington, DC, 2016)
Amidst a turbulent regional political and security environment, Jordan wrestles with sluggish growth and high unemployment. A number of risks materialized in 2015, particularly related to security spillovers and their negative impact on tourism, construction, investment and exports. As such, the economy slowed down for the first time since 2010, further widening Jordan’s output gap, with growth declining from 3.1 percent in 2014 to 2.4 percent for 2015. However, growth remained otherwise broad-based. The largest contributions to growth came from ‘finance and insurance services’, ‘transport, storage and communications’, ‘producers of government services’, ‘electricity and water’ and manufacturing sectors although it was ‘mining and quarrying’ and ‘electricity and water’ that saw the highest growth rates in 2015. Unemployment reached an average of 13.0 percent in 2015, 1.1 percentage points wider compared to 2014. Growth is projected to rebound slightly, to an average of 3.3 percent over 2016-2018, provided no further spillovers from the Syrian crisis occur. Chiefly, Jordan will need to continue managing repercussions from the regional security and political situation, and the challenges of hosting 1.37 million Syrians (of which 639,704 registered refugees). Additionally, since Jordan benefits from the GCC for remittances, exports, FDI and grants, large sources of foreign exchange - persistently low oil prices are a risk for Jordan this year and in the medium term. Weak global demand may impact demand for Jordan’s mining exports. Furthermore, the willingness and speed of reform implementation particularly to improve the business climate will be crucial to attract Jordan’s investment aspirations.